1999
DOI: 10.1074/jbc.274.8.4778
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Related Peptide Agonist, Partial Agonist, and Antagonist Occupy a Similar Binding Pocket within the Cholecystokinin Receptor

Abstract: The molecular basis of ligand binding to receptors provides important insights for drug development. Here, we explore domains of the cholecystokinin (CCK) receptor that are critical for ligand binding, using a novel series of fluorescent photolabile probes, receptor proteolysis, and rapid high resolution separation of peptide fragments by capillary electrophoresis. Each probe incorporated the same fluorophore and a photolabile p-benzoylphenylalanine at the amino terminus of the pharmacophoric domain (residue 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Indeed, each peptide was able to compete for the binding of each of the other peptide ligands, supporting their generally similar position of docking to the receptor. This was further supported by the covalent labeling of the same general domain of the CCK receptor by each of these probes, as determined by the pattern of capillary electrophoresis of labeled fragments after cyanogen bromide cleavage (9). That domain was definitively identified in a later study (8).…”
Section: Lifetime Measurements For Fluorescent Ligandsmentioning
confidence: 62%
See 2 more Smart Citations
“…Indeed, each peptide was able to compete for the binding of each of the other peptide ligands, supporting their generally similar position of docking to the receptor. This was further supported by the covalent labeling of the same general domain of the CCK receptor by each of these probes, as determined by the pattern of capillary electrophoresis of labeled fragments after cyanogen bromide cleavage (9). That domain was definitively identified in a later study (8).…”
Section: Lifetime Measurements For Fluorescent Ligandsmentioning
confidence: 62%
“…The current fluorescence studies are a direct extension of a unique series of photoaffinity labeling studies of this receptor (9). In those studies, a structurally similar peptide agonist, a partial agonist, and an antagonist were each modified to accommodate a photolabile benzoyl-phenylalanine at their amino terminus in position 24 (of the standard CCK-33 numbering scheme).…”
Section: Lifetime Measurements For Fluorescent Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the angiotensin AT 1 and the endothelin ET A receptors, minimal overlapping binding sites between peptide agonists and antagonists have been demonstrated, respectively (40,41). Very recently, it has been observed that structurally related peptide agonist, partial agonist, and antagonist occupy a similar binding pocket within the rat cholecystokinin CCK-A receptor (42). Similarly, we describe in the present study major transmembrane overlapping binding sites in the V 1a vasopressin receptor for both peptide agonist and two linear peptide antagonists.…”
Section: Receptor Interactions As Observed In the Modelmentioning
confidence: 99%
“…These probes have similar primary structures, sharing the critical amino acid functional groups that have been shown to be responsible for the specificity of CCK receptor binding, pointing toward similarity in the position of their docking to this receptor. Additional support for similar docking comes from photoaffinity labeling studies in which the same segment of the CCK receptor was covalently labeled by each of three analogous photolabile probes, with sites of covalent attachment through a benzoyl phenylalanine at position 24, the same position as that of the fluorescence indicator in the probes used in the current work (16). For still further validation of the similarity of the docking of these probes and for purposes of registration, in the current work all three of these structurally similar ligands resulted in a fixed distance measured between the fluorophore at the amino terminus of the probes at position 24 and receptor residue 94 within the intramembranous region of helix two.…”
Section: Development and Characterization Of Receptor Probes-the Fluomentioning
confidence: 99%